2018
DOI: 10.1152/ajpheart.00299.2017
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of 2-arachidonoylglycerol on whole blood platelet aggregation and on cerebral blood flow after a focal ischemic insult in rats

Abstract: This version is available at https://strathprints.strath.ac.uk/62815/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Its levels in WKY and SHAM were 220 and 75 times higher than the concentration of the best-known endocannabinoid AEA, respectively. This is an important observation in the light of recent publications that 2-AG in vivo worsens heart function after acute myocardial infarction [47], increases the severity of the cerebral blood flow deficit [55] or promotes atherogenesis [56] on the one hand but ameliorates inflammatory stress-induced insulin resistance in cardiomyocytes on the other [57]. Unfortunately, there are only limited data regarding the cardiovascular effects of endocannabinoids other than 2-AG and AEA.…”
Section: Generalmentioning
confidence: 89%
“…Its levels in WKY and SHAM were 220 and 75 times higher than the concentration of the best-known endocannabinoid AEA, respectively. This is an important observation in the light of recent publications that 2-AG in vivo worsens heart function after acute myocardial infarction [47], increases the severity of the cerebral blood flow deficit [55] or promotes atherogenesis [56] on the one hand but ameliorates inflammatory stress-induced insulin resistance in cardiomyocytes on the other [57]. Unfortunately, there are only limited data regarding the cardiovascular effects of endocannabinoids other than 2-AG and AEA.…”
Section: Generalmentioning
confidence: 89%
“…In vitro experiments have demonstrated that 2-AG acts as a platelet agonist, promotes platelet activation and aggregation and is also released by the activated platelets 33 34 ; this finding was validated in vivo with a murine study where exogenous 2-AG administration (micromolar doses) induced platelet aggregation and worsened cerebral blood flow in the first hour of middle cerebral artery occlusion 35 . In our study we also observed that all patients who underwent embolectomy (all procedures resulted in successful recanalization) did not have significant elevations of 2-AG in the subacute phase.…”
Section: Discussionmentioning
confidence: 88%
“…has demonstrated an intimate connection between poststroke CBF and 2-AG signaling, and further work should be done to unpack this relationship in order to better predict the full effects of endocannabinoid therapeutics in human. [31] Second, Rivers-Auty et al . have cast doubt on the idea that CB2 agonism can reduce brain damage associated with hypoxia-ischemia, and further work is needed to examine the true potential of CB2 agonism as a promising poststroke neuroprotectant.…”
Section: Resultsmentioning
confidence: 99%
“…performed blinded measurements of CBF. [31] They found that CBF was severely reduced in the 2-AG group when compared to vehicle controls for up to 4 h following the ischemic insult. These results further suggest that blocking the effects of 2-AG, the main endogenous ligand for CB1R and CB2R could play a neuroprotective role in stroke.…”
Section: Cannabinoid Receptor Agonists and Antagonists As Stroke Neurmentioning
confidence: 99%